ANTIHEROES AND THE DIALECTIC OF FREEDOM–‎ORDER: A COMPARATIVE STUDY OF THE THOUGHTS OF ‎EREN YEAGER, THANOS, AND THE TEMPLARS–‎ASSASSINS - Hidayat, Muhammad; Kustati, Martin; Bashori (International Journal of Multidisciplinary Reseach, 2025)
This study explores the ideological dimensions of antiheroes in contemporary popular culture by conducting a comparative analysis of Eren Yeager, Thanos, and the Assassin–Templar conflict in Assassin’s Creed. Eren represents radical freedom driven by collective trauma and existential threat, often navigating moral ambiguity between liberation and destruction. Thanos embodies extreme utilitarian order, prioritizing systemic stability and the “greatest good” over individual moral agency, reflecting authoritarian and technocratic problem-solving logic. Meanwhile, the Assassin–Templar conflict presents a nuanced dialectic between liberty and control, with both factions justifying morally ambiguous actions to achieve societal balance. This research examines how these narratives articulate ethical dilemmas, ideological motivations, and the tension between freedom and order, demonstrating that modern antiheroes serve as critical lenses for evaluating complex political, social, and philosophical questions. The findings indicate that popular media provides a reflective space in which audiences negotiate morality, authority, and autonomy, highlighting the relevance of antiheroes in understanding contemporary ethical and ideological challenges.